Experimental investigation of spray characteristics of gliding arc plasma airblast fuel injector. (1st June 2021) - Huang, Shengfang; Wu, Yun; Zhang, Kai; Jin, Di; Zhang, Zhibo; Li, Yinghong
Highlights: A gliding arc plasma airblast fuel injector is proposed. Mean drop size of kerosene largely decreases especially in the near-field spray. Droplet uniformity index of kerosene spray was increased. Spray cone angle was obviously enlarged. Abstract: High atomization quality plays a vital role in combustion performance enhancement for aero-engines and ramjets. Low enthalpy and low pressure at low flight Mach number result in poor atomization quality of airblast fuel injector. Underlying mechanism of how plasma assisted combustion on spray characteristics still remains unclear. In present study, a novel gliding arc plasma airblast fuel injector is proposed for atomization quality improvement of airblast fuel injector in order to achieve high combustion efficiency, low pollutant emission, and to prolong life of injectors. Spray and atomization characteristics of aviation kerosene (RP-3) under different working conditions which includes gliding arc plasma excitation, air flow velocity and air/fuel ratio were investigated. A string-like gliding arc discharge plasma column was generated between the two electrodes mounted at the exit port plane of plasma airblast fuel injector. Macroscopic and microscopic spray characteristics were studied by simultaneous LIF/MIE technique and particle/droplet image analysis (PDIA) system. Results reveal that mean droplet size were decreased with increase of air flow velocity and air/fuel ratio. Influenced by the thermal and transport effect of gliding arc plasma excitation, more homogeneous fuel spray with smaller mean drop size and greater spray cone angle was witnessed. Sauter mean diameter was decreased by around 50% at 17 m/s, while droplet uniformity index and spray cone angle were increased by up to 24.6% and 35%, respectively. The gliding arc plasma mainly take effect on reducing mean droplet size of kerosene in the near-field spray (<20 mm) which is very near from the ignitor to improve high initial evaporation rates for rapid ignition and combustion efficiency improvement.